Food manufacturing processes and technical data used in the exposure assessment of food enzymes - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2023)
Abstract Food enzymes are used for technical purposes in the production of food ingredients or foods‐as‐consumed. In the European Union, the safety of a food enzyme is evaluated by EFSA on the basis of a technical dossier provided by an applicant. Dietary exposure is an integral part of the risk assessment of food enzymes. To develop exposure models specific to each food manufacturing process in which food enzymes are used, different input data are required which are then used in tandem with technical conversion factors. This allows the use levels of food enzyme to be related to food consumption data collected in dietary surveys. For each food manufacturing process, EFSA identified a list of food groups (FoodEx1 classification system) and collated technical conversion factors. To ensure a correct and uniform application of these input data in the assessment of food enzyme dossiers, stakeholders were consulted via open calls‐for‐data. In addition to publishing and updating the identified input parameters on an annual basis, single‐process‐specific calculators of the Food Enzyme Intake Models (FEIMs) have been developed. These calculators have been deposited at https://zenodo.org/ since 2018 for open access. By 2023, EFSA had compiled the input data for a total of 40 food manufacturing processes in which food enzymes are employed. In this document, the food manufacturing processes are structured, food groups classified initially in the FoodEx1 system are translated into the FoodEx2 system, and technical factors are adjusted to reflect the more detailed and standardised FoodEx2 nomenclature. The development of an integrated FEIM‐web tool using this collection of input data is released in 2024. This webtool is able to estimate the exposure to the food enzyme–total organic solids (TOS) when employed in single or multiple food manufacturing processes.